English for Engineering Students: A Survey of Pokhara University - Chhetry, Tek Bahadur (The Educator Journal, 2022)
This paper’s main objective was to examine the perception of the English language needs of the engineering students at Pokhara University, Kaski, Nepal, as a part of a curriculum review. The study was carried out to identify the perceived notion of English among the students for their career development, assess if the current curriculum meets the standards, and identify the flaws in the curriculum concerning other universities in Nepal. Both quantitative and qualitative approaches were used as mixed methods. A cross-sectional survey questionnaire was administered among engineering students of Pokhara University in one constituent college and 14 affiliated colleges. By random sampling method, 326 responses were collected and analyzed through SPSS V.20 for quantitative data, and experts’ opinions were sought from ten responses with purposive sampling for qualitative data. The study’s findings showed that the English curriculum designed for engineering students in Pokhara University doesn’t fulfill the professional needs of the engineering profession. The experts recommended various new topics to incorporate into the syllabus after carefully examining the differences among various curricula of other universities. In addition, teaching English without the effectiveness of labs and tutorials in three credit hours seems illogical. This report will be helpful to the Curriculum Development Center of Pokhara University, the subject committee of English language, planners, teachers, experts and other policymakers.